AKIBAT PUTUSNYA HUBUNGAN PERKAWINAN TERHADAP HAK SUAMI ATAS HARTA BERSAMA YANG MASIH DALAM PROSES ANGSURAN (STUDI PUTUSAN PENGADILAN NEGERI TANGERANG NOMOR 482/PDT.G/2017/PN.TNG JO. PUTUSAN PENGADILAN TINGGI BANTEN NOMOR 105/PDT/2018/PT.BTN - Sherinne Sherinne; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
The result of marital relationship between husband and wife broke up that commonly influences to the marital’s joint property. Marital’s joint property after the dissolution of marital relationship is usually distributed between husband and wife in balance. This case in Decision of the Tangerang State Court No. 482/Pdt.G/2017/PN.Tng Jo. Decision of the Banten High Court No. 105/PDT/2018/PT.BTN, dissolution of marital relationship between husband and wife still have the obligation to pay the house installments. After the dissolution of marital relationship, the ex-husband had good faith by paying the house installments until paid off. However, the ex-husband did not get his right to the fulfillment of achievements in paying that house installment. The research method used normative legal research by examining literature through statute approach. The result in legal research is ex-husband has still his right to house installment even though between husband and wife had been already broken up of marital relationship. This is because the house was obtained at the time of marriage between husband and wife, mainly the husband had paid the house installments after the dissolution of marriage. The results of the house installment must be distributed between ex-husband and ex-wife in accordance to the achievements of the house installment that paid at the time of marriage and dissolution of marriage.